2019
DOI: 10.3390/genes10080566
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Models Assessing Mammary Tumor Prevention by Soy or Soy Isoflavones

Abstract: While epidemiological studies performed in Asian countries generally show that high levels of dietary soy are associated with reduced breast cancer risk, studies in Western countries have typically failed to show this correlation. In an attempt to model the preventative actions of soy on mammary tumor development, rodent models have been employed. Thirty-four studies were identified that evaluated the impact of soy products or purified soy isoflavones on mammary tumor initiation (studies evaluating established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…It is well known that there are a number of risk factors for breast cancer (e.g., an advanced age or viral infection) (21). The dietary quality and habits are also one of the factors affecting breast cancer (e.g., the consumption of red meat, ultra-processed sugary products, sulforaphane, vitamin D, calcium, soy isoflavone) (18,(22)(23)(24)(25). Recently, the influence of the quality of daily foods on breast cancer has attracted considerable attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that there are a number of risk factors for breast cancer (e.g., an advanced age or viral infection) (21). The dietary quality and habits are also one of the factors affecting breast cancer (e.g., the consumption of red meat, ultra-processed sugary products, sulforaphane, vitamin D, calcium, soy isoflavone) (18,(22)(23)(24)(25). Recently, the influence of the quality of daily foods on breast cancer has attracted considerable attention.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale cohort study carried out in France revealed that the intake of ultra-processed sugary products was associated with the incidence of breast cancers (23). By contrast, sulforaphane extracted from broccoli, vitamin D, calcium and soy isoflavone have been reported to function as possible cancer-preventive agents (18,24,25). Therefore, it seems that the constituents of foods consumed on a daily basis play a role in breast carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, isoflavone is produced by an oncogene and functions as an inhibitor of tyrosine protein kinase [ 45 ]. Among the soybean isoflavones, genistein inhibits the growth of cells that cause breast, colon, lung, prostate, and skin cancers in vitro ( Figure 5 ) [ 36 , 46 ]. In addition, genistein inhibits the formation of boils by preventing vasculogenesis, thus blocking the supply of oxygen or nutrients [ 47 ].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Since it is difficult to control for the contributions of other lifestyle factors to breast cancer risk in humans and human prevention trials would take decades to complete, several studies have utilized rodent models to investigate the impact of soy on mammary tumor development. Animal models using chemical carcinogens or oncogenic transgenes have showed mixed results (reviewed in (17)) with some studies showing that soy decreases tumor latency or increases tumor incidence while other studies demonstrate that soy protects against mammary tumor development or had no effect.…”
Section: Introductionmentioning
confidence: 99%